(3TQM CHjGJ GdeaUds - (3eLghds; (3eMehO Hf YeQ Hf eMeO Hf CMeO GdNhGQRej GdReNTQqj, LGQ Gddg, CHh GdbGSe,(B538 (3g`s ((3HGHG Ydj s)
(3ChdgG (B:s
(3hHYO, adG jNai Cf cJGH GdeaUd aj GdEYQGH cJGH dYeQj cGad GdebGUO dG jTcd Ydi GdYGQa s
(3BNQgG (B:s
(3Cf jchf YGL eJYOjkG ef bhdge YGL GdHYjQ eYGLG Cj YWa QCSg aGfYGL djS HHYjO hQhGjI GHf Lfj hYLfG jDjOg ef MjK GdeYfi s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs